ISOLATION AND STRUCTURE ELUCIDATION OF A NEW OLEANOLIC ACID AND ITS SAPONINS FROM Thylacospermum caespitosum - Muhammad Hanafi (Research Center for Chemistry - LIPI, 1997)
A new oleanollc acid and its saponins have been isolated from methanol and ether extract of the whole plant of cushion plant T. caespltosum. The compounds were established as olean-12-en-3b-16a-diol-23,28-dioic acid (1), 3jJ-O-jJ-D-glucopyranosylolean12-en-16a-diol-23-doic acid (2), and 28-O-B-D-glucopyranosylolean–12-en3b, 16a-diol-23-dioc acid (3), which are trivial named as thylacospermic acid (1), thylacospermicoside A (2) and thylacospermicoside B (3), respectively. Three known steroids namely 22,23-dihydrospinasterol (4), a-spinasterol (5), and 3jJ-OjJ-D-glucopyranosylspinasterol(6) [lJ and the mixture of phytoceramides (7) [2, 8] were also isolated from the ether extract. The compounds were identified based on chemical and spectroscopic methods. This is the first report on the isolation of the compounds from genus Thylacospermum.